A rare presentation of Sinonasal Undifferentiated Carcinoma with brain metastasis and para-aortic mass - Sujata Sarangi; Sudeep Khera; Vikarn Vishwajeet; Vikas Meshram; Puneet Setia; Abhishek Malik (University of São Paulo, 2021)
Sinonasal Undifferentiated carcinoma (SNUC) comprises 3% of the head and neck tumors, including metastatic neoplasms. Herein we report the case of a 60-year-old male who was brought dead to our institute with previous records of a contrastenhanced CT scan of the brain and MRI with evidence of tumor in the maxillary sinus with intracranial extensions. The histopathological examination of the mass in the maxillary sinus proved to be SNUC with metastases to the brain, lungs, and around the aorta. These tumors are undifferentiated and are distinct from other poorly differentiated tumors in deriving their origin from the Schneiderian epithelium. The aggressive nature of the tumor renders the prognosis quite dismal. SNUCs need to be early recognized and distinguished from other poorly differentiated carcinomas with the help of immunohistochemistry.